The unconditioned fear response in dystrophin-deficient mice is associated with adrenal and vascular function - Angus Lindsay; Aaron P. Russell (Scientific Reports, 2023)
Abstract Loss of function mutations in the gene encoding dystrophin elicits a hypersensitive fear response in mice and humans. In the dystrophin-deficient mdx mouse, this behaviour is partially protected by oestrogen, but the mechanistic basis for this protection is unknown. Here, we show that female mdx mice remain normotensive during restraint stress compared to a hypotensive and hypertensive response in male mdx and male/female wildtype mice, respectively. Partial dystrophin expression in female mdx mice (heterozygous) also elicited a hypertensive response. Ovariectomized (OVX) female mdx mice were used to explain the normotensive response to stress. OVX lowered skeletal muscle mass and lowered the adrenal mass and zona glomerulosa area (aldosterone synthesis) in female mdx mice. During a restraint stress, OVX dampened aldosterone synthesis and lowered the corticosterone:11-dehydrocorticosterone. All OVX-induced changes were restored with replacement of oestradiol, except that oestradiol lowered the zona fasciculata area of the adrenal gland, dampened corticosterone synthesis but increased cortisol synthesis. These data suggest that oestrogen partially attenuates the unconditioned fear response in mdx mice via adrenal and vascular function. It also suggests that partial dystrophin restoration in a dystrophin-deficient vertebrate is an effective approach to develop an appropriate hypertensive response to stress.